Avaliação da resistência e da qualidade óssea em ratos submetidos ao uso de inibidores do cotransportador sódio-glicose 2 - MARCHI, Ana Elisa Rebeschini de (2022)
Bone integrity can be compromised in Diabetes Mellitus (DM) and allows the occurrence of bone fractures. Many drugs are used for the treatment of DM and SGLT-2 inhibitors have been associated with improved glycemic control with reduced cardiovascular risk. However, some studies have associated its use with bone impairment, demonstrating uncertainties. Thus, in this study, we analyzed whether there are alterations in the quality and resistance of bones in healthy rats submitted to the use of dapagliflozin, empagliflozin and canagliflozin. Forty Wistar rats distributed in four experimental groups were used: control group (saline solution); Dapa group (dapagliflozin 10 mg/kg/day); Empa group (empagliflozin 10 mg/kg/day); Cana group (canagliflozin at 20 mg/kg/day). The animals were weekly weighed (8 weeks) and serum tests were performed, such as glucose, alkaline phosphatase, total and ionic calcium, phosphorus and magnesium, Raman spectroscopy and mechanical flexion test of three. The Dapa and Cana groups had higher ionic calcium and alkaline phosphatase values. The Raman data did not show differences, while the mechanical test revealed that the Empa group obtained less deformation (absolute and relative), less energy absorption at fracture and greater stiffness (extrinsic and intrinsic). It is concluded that, in healthy rats, not submitted to the bone effects of DM, SGLT2 inhibitors can indirectly promote changes in bone metabolism.